(untitled) (Revista cientifica In Vestigium Ire, 2020)
Disaster risk management is evaluated from a macro territorial approach and information is lost on the local aspect of the population. There are groups of vulnerability indicators at the national and international level that can be adapted to the local situations of the population, with the aim of gathering information for territorial planning. A list of national and international indicators was obtained which, under the approach of the theory of complexity, were considered applicable at a local level, with the requirement that the indicators be easily applicable by communities and local governments in environments where there is a shortage of data. The indicator Degree of Social Vulnerability associated with disasters (GVS), selected to evaluate vulnerability at a local scale in the El Tambo neighborhood, north-west of the city of Monteria, provides information on the population’s perception of the existing hazards in the community and some general aspects of the population that contribute to reducing social vulnerability